The Influence Of Entrepreneurial Orientation And Market Orientation On The Performance Of Tempe Micro Small And Medium Enterprises (Umkm) In Langsa City - Saputra, Iskandar; Jakfar, Fajri; Hakim, Lukman (PT. Hafasy Dwi Nawasena, 2024)
This research aims to identify and analyze the influence of entrepreneurial orientation and market orientation on the performance of tempeh MSMEs in Langsa City. This research was conducted for two months, namely from February to March 2024, with a quantitative approach. The population studied included all tempeh MSME business actors in Langsa City, totaling 118 MSMEs. From this sample population, 54 MSMEs were selected purposively to ensure that the sample used was relevant and could provide significant information in the context of this research. The data collected in this research is primary data, obtained directly from the original source through various methods, including interviews, questionnaires and opinion polls. Apart from that, the results of direct observations of related objects or events are also used as part of primary data. This data was then analyzed to understand which entrepreneurial orientation, which includes innovation, proactivity, and the courage to take risks, as well as market orientation, which includes understanding consumer needs and preferences, can influence the performance of tempeh MSMEs in Langsa City. It is hoped that the results of this research will provide in-depth insight into the importance of entrepreneurial orientation and market orientation in improving MSME business performance. Thus, it is hoped that these findings can become the basis for formulating more effective business strategies, to support the development and sustainability of tempeh MSMEs in Langsa City, especially in facing increasingly competitive market challenges.